A Documentary History of Art, Volume 1 The Middle Ages and the Renaissance - Holt, Elizabeth Gilmore (Princeton University Press, 2024)
An illuminating one-volume compendium of primary documents on the art of medieval and Renaissance EuropeThis unique collection brings together notebooks, letters, treatises, and contracts dealing with the art of the Middle Ages and Renaissance, providing extraordinary insights into the personalities and conditions of the times and revealing the stylistic and philosophical concerns that evolved during these intensively creative eras. These documents, many of them available here in English for the first time, range from Raoul Glaber's famous 1003 treatise on the synthesis of old and new art forms to Durand's essay on Christian symbolism in art and the writings of Leonardo and Dürer on anatomy, perspective, and the recreation of reality. They trace how a medieval conception of life that was inspired, oriented, and dominated by the church evolved gradually into the great reawakening of the Renaissance in which humankind itself assumed primary importance in Western art
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Aug 2024)
Keywords: ART / History / General; Art -- History -- Sources; Art, Medieval; Art, Renaissance